Reconceptualizing Global Citizenship in Turkish Social Studies Textbooks With a Focus on Social Justice - Kilinc, Emin; Eizadirad, Ardavan; Straub, Jennifer (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2024)
This study examines the integration of global perspectives in the social studies textbooks used in Grades 4 to 7 in Turkey using content analysis as a methodology. The analysis focuses on seven mandatory textbooks distributed across the country and the big ideas and themes reinforced as official knowledge promoted by the state. The findings reveal both strengths and weaknesses in the textbooks’ content and approach to teaching about global connections. While the textbooks aim to promote global citizenship, cultural understanding, and economic relationships, they also perpetuate nationalistic perspectives, stereotypes, and biased coverage of various forms of inequality and social injustice. Failure to critically analyze diverse cultures, perpetuation of biased views, negative portrayal of Western culture, and a lack of comprehensive coverage of inequality are some of the arising issues and emerging themes identified. Additionally, the textbooks neglect explicit discussions about equity and social justice and connections to the civic engagement of citizens. These findings promote passive citizenship and underscore the need for greater attention to inclusivity, cultural understanding, and comprehensive coverage of global issues and social justice in social studies education in Turkey and beyond as it relates to international relations.